ANALISIS GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI UNTUK MENINGKATKAN KINERJA KARYAWAN DALAM PERSPEKTIF EKONOMI ISLAM (STUDI KASUS TOSERBA YOGYA KOTA BANJAR) - Vina Erdiani; Pepe Iswanto (Syari'ah Economics, 2019)
This study aims (1) to determine the leadership style to improve employee performance in the perspective of Islamic economics in Toserba Yogya, Banjar City; (2) to know the organizational culture to improve employee performance in the perspective of Islamic economics at the Yogya Department Store, Banjar City; and (3) to determine the performance of employees at the Yogya department store, Banjar City in the perspective of Islamic economics. Data were collected through observation and interviews with store managers, employees and consumers of the Yogya Banjar Department Store. The results showed that the leadership styles at the Toserba Yogya Banjar include democratic leadership style, analytical leadership style (analytical), and assertive leadership style (assertive). In the view of Islam, economics or iqtishad comes from the word "qosdun" which means balance (equilibrium) and justice (equally balanced). According to the author, Leaders at Toserba Yogya Banjar have been fair in their duties as leaders, then always respect employees starting from small things so as to make employees motivated. At the Yogya Banjar department store itself, according to the author, the organizational culture has implemented values ​​that do not conflict with Islamic economics, including in terms of the company's core values, namely "honest, loyal, and humble" which are also always applied and taught in Islamic economics. . In addition, for monotheism (faith in God) in the organizational culture at the Yogya Banjar Department Store, it is implemented, among others, by doing prayers every day, both morning, afternoon and evening. And for justice itself in the organizational culture itself can be seen by fulfilling the rights for employees so that employees fulfill their obligations in their work. The goal of Islamic economics is mashlahah (benefit) for mankind. In this case, all members (both leaders and employees) always try their best in carrying out their duties at work and cooperate well in completing their work by helping each other between divisions.